2021
DOI: 10.3892/etm.2021.9905
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy enhances bone regeneration compared with conventional therapy in a rabbit radius gap‑healing model

Abstract: Negative pressure wound therapy (NPWT) has been recognized as an effective method for the treatment of intractable wounds. However, its effects on bone healing remain to be elucidated. Our previous study demonstrated that NPWT induced cell proliferation and osteoblastic differentiation of rat periosteum-derived mesenchymal stem cells (P-MSCs). It was reported that following NPWT treatment, the expression of the mechanotransduction molecule integrin β5 is increased, indicating that NPWT may serve an active role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Further, we conducted the verification of proliferation and osteogenic differentiation of BMSCs, and the results confirm that −120 mmHg NP demonstrated the optimal osteogenic effect compare with other NP scales ( Figure 14 ). This osteogenic differentiation was also verified by clinical practice and experimental findings ( Kim and Lee, 2019 ; Zhu et al, 2021 ). One would argue that osteogenesis is a combined effect of fluid shear stress and NP within the marrow cavity; however, studies have shown that hydrodynamic shear stress induces prostaglandin synthesis, activation of kinases ERK and JNK, and mRNA expression of Runx2, ALP, COL1A1, VEGF, BMP-2, BMP -7 and TGF-β1, but does not stimulate cell proliferation in osteoblasts and MSCs ( Kreke et al, 2008 ; Sharp et al, 2009 ; Yu et al, 2014 ).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Further, we conducted the verification of proliferation and osteogenic differentiation of BMSCs, and the results confirm that −120 mmHg NP demonstrated the optimal osteogenic effect compare with other NP scales ( Figure 14 ). This osteogenic differentiation was also verified by clinical practice and experimental findings ( Kim and Lee, 2019 ; Zhu et al, 2021 ). One would argue that osteogenesis is a combined effect of fluid shear stress and NP within the marrow cavity; however, studies have shown that hydrodynamic shear stress induces prostaglandin synthesis, activation of kinases ERK and JNK, and mRNA expression of Runx2, ALP, COL1A1, VEGF, BMP-2, BMP -7 and TGF-β1, but does not stimulate cell proliferation in osteoblasts and MSCs ( Kreke et al, 2008 ; Sharp et al, 2009 ; Yu et al, 2014 ).…”
Section: Discussionsupporting
confidence: 71%
“…NPWT promotes angiogenesis and granulation in part by the strain-induced production of growth factors and cytokines, and most of these findings were recognized under an NP of −120 or −125 mmHg ( Glass et al, 2014 ), which is most effective for soft-tissue wounds ( Argenta and Morykwas, 1997 ; Morykwas et al, 1997 ; Morykwas et al, 2001 ; Chen et al, 2017 ; Liu et al, 2018b ; Wu et al, 2022 ). In a bone tissue, which is a hard tissue, BMSCs osteogenesis activation and osteoclasts inhibition were also found under a short time continuous NP of −125 mmHg via kinds of osteogenic factors, such as vascular endothelial growth factor, bone morphogenetic protein-2, osteopontin, mechanotransduction molecule integrin β5, alkaline phosphatase, collagen1α2 and hypoxia-inducible factor-1α( Zhu et al, 2014 ; Wang et al, 2020 ; Zhu et al, 2021 ). The mechanisms by which NP activates mechanotransductive signaling pathways and stimulates the osteoblastic phenotype have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depolarization and hyperpolarization after mechanical stimulation were inhibited by integrin α v , α 5 , β 1 , and β 5 blockers [104]. Negative pressure wound therapy (NPWT) has been recognized as an effective method for healing bone injury [105][106][107]. Cell experiments demonstrated that NPWT promoted the proliferation and osteogenic differentiation of periosteum-derived MSCs.…”
Section: Integrins Mediate Mechanotransduction and Regulate Bone Meta...mentioning
confidence: 99%
“…Vascular endothelial growth factor and angiopoietin-2 (Ang-2) levels in the wound are much higher in NPWT, which may be caused by the closed and hypoxic environment ( Ma et al, 2016 ; Yang et al, 2021 ; Zhu et al, 2021 ). Negative pressure provides effective and continuous power to the local circulation of the wound, reducing the seroma and hematoma, as compared with traditional dressing ( Nagata et al, 2018 ; Mangelsdorff et al, 2019 ; Zwanenburg et al, 2020 ; Bueno-Lledo et al, 2021 ).…”
Section: Npwt Mechanismmentioning
confidence: 99%